Amniotic Membrane in the Treatment of Burns - Ahmad Sukari, Halim; Ehfa, Bujang-Safawi; Arman Zaharil, Mat Saad (Springer Netherlands, 2015)
Burn wound dressing represents an important aspect of burn care. The various inherent features of amniotic membrane proved to be useful as it contributes towards the attributes of an ideal dressing. This biological dressing is inexpensive, able to enhance re-epithelialization, readily available and stored, hence rendering it suitable for a wide range of burn wound treatment. The different preparations of amniotic membrane provide additional benefit whereby clinicians can have a range of product to choose from. Pain relief, good wound adherence and conformability further increase the importance of amnion as burn wound dressing. The versatility and efficacy of the amnion makes it an attractive option despite of the enormous range commercially available wound management products in the market. This chapter presents a review of the various aspects of amniotic membrane for burn wound treatment.